An artists' perspectives on natural interactions for virtual reality 3D sketching - Rodriguez, Richard, author; Sullivan, Brian T., author; Machuca, Mayra Donaji Barrera, author; Batmaz, Anil Ufuk, author; Tornatzky, Cyane, author; Ortega, Francisco R., author; ACM, publisher (Colorado State University. Libraries, 2024)
Virtual Reality (VR) applications like OpenBrush offer artists access to 3D sketching tools within the digital 3D virtual space. These 3D sketching tools allow users to "paint" using virtual digital strokes that emulate real-world mark-making. Yet, users paint these strokes through (unimodal) VR controllers. Given that sketching in VR is a relatively nascent field, this paper investigates ways to expand our understanding of sketching in virtual space, taking full advantage of what an immersive digital canvas offers. Through a study conducted with the participation of artists, we identify potential methods for natural multimodal and unimodal interaction techniques in 3D sketching. These methods demonstrate ways to incrementally improve existing interaction techniques and incorporate artistic feedback into the design.
Keywords: virtual reality; gestures; speech; multimodal interaction; 3D sketching